Types Of Refugia That Effectively Preserve Parasitoid Diadegma semiclausum In Control Plutella xylostella Cabbage Pests In Tomohon City - Dumalang, Sherlij; Wanta, Noni N.; Turang , Defly A. S. (Jurnal Agroekoteknologi Terapan, 2024)
Refugia is a plant used in plant cultivation that provides food in the form of nectar and honeydew needed by parasitoid imago so that it can survive its life and can increase its effectiveness. Parasitoids. Diadegma semiclausum is one of the parasitoids that can suppress the population of P. xylostella pests on cabbage plants to a non-detrimental extent or below the economic threshold. The purpose of this study was to determine the types of refugia that effectively preserve the parasitoid D. semiclausum around Tomohon City cabbage plants. The research method used is the survey method. Observations were carried out using self-adhesive traps, insect nets, and direct observations on plants that produce flowers vegetables, flowers, and weeds around cabbage plants in Paslaten, Rurukan, Kakaskasen I, and Wailan Villages. The data obtained were analyzed descriptively to determine the type of plant that invited the most presence of the parasitoid insect D. semiclausum as an effective refugium. Based on observations, it turns out that the effective refugia for D. semiclausum parasitoids is the Green Mustard plant. Plants that are visited by many other insects are Green Mustard plants, Legetan Weeds, Japanese Jasmine, and Carrots. Keywords: Refugia, Pest, Parasitoid, D. semiclausum, P. xylostella Abstrak Refugia merupakan tanaman yang digunakan dalam budidaya tanaman yang menyediakan makanan berupa nektar dan embun madu yang dibutuhkan oleh imago parasitoid sehingga dapat melangsungkan kehidupannya dan dapat meningkatkan efektifitasnya. Parasitoid. Diadegma semiclausum adalah salah satu parasitoid yang dapat menekan populasi hama P. xylostella pada tanaman kubis sampai batas yang tidak merugikan atau di bawah ambang ekonomi. Tujuan dari penelitian ini adalah untuk mengetahui jenis-jenis refugia yang efektif melestarikan parasitoid D. semiclausum di sekitar pertanaman kubis Kota Tomohon. Metode penelitian yang digunakan adalah metode survey. Pengamatan dilakukan dengan menggunakan perangkap berperekat, net serangga dan pengamatan secara langsung pada tanaman yang menghasilkan bunga baik sayuran, bungaan dan gulma yang ada di sekitar pertanaman kubis di Desa Paslaten, Rurukan, Kakaskasen I dan Wailan. Data yang diperoleh dianalisis secara deskriptif untuk menentukan jenis tanaman yang mengundang paling banyak kehadiran serangga parasitoid D. semiclausum sebagai refugia efektif. Berdasarkan hasil pengamatan ternyata bahwa refugia yang efektif bagi parasitoid D. semiclausum adalah tanaman Sawi Hijau. Tanaman yang banyak dikunjungi serangga lainnya adalah tanaman Sawi Hijau, Gulma Legetan, Melati Jepang dan Wortel. Kata Kunci: Refugia, Hama, Parasitoid, D. semiclausum, P. xylostella